New species of tree cricket Oecanthus Serville, 1831 (Orthoptera: Grylloidea) from Southern Brazilian Atlantic Forest, with bioacoustics - Zefa, Edison; Acosta, Riuler Corrêa; Timm, Vítor Falchi; Costa, Maria Kátia Matiotti Da (Zootaxa, 2022)
Tree Crickets, Oecanthus Serville, 1831 have a worldwide distribution, and are known as Tree Crickets because they are common in the treetops, even though many species occur in different strata of forest, and also in open fields. In this work we describe a new species of Oecanthus from Southern Brazil, based on the most significant diagnostic structures in the ocanthine taxonomy, such as the phallic sclerites and metanotal gland morphology, as well as calling song. The new species herein described has a distinct faint red spot between the eyes, a metanotal gland with a triangular posterior median lobe with the apex curved up and forward, the median lophi of pseudepiphallus slightly elongate with an U-shaped invagination, and the ectophallic distal arc prolongation with the posterior apex U-bifurcated. The calling song stands out among the local stridulating crickets for alternate a regular and an irregular train of chirps. Illustrations of the external morphology, information about type specimens, material examined, measurements, and spectrogram of the calling and courtship songs is provided.